Clozapine Induced Disturbances in Hepatic Glucose Metabolism: The Potential Role of PGRMC1 Signaling - Cao, Ting; Chen, Qian; Zhang, BiKui; Wu, XiangXin; Zeng, CuiRong; Zhang, ShuangYang; Cai, HuaLin (Frontiers in Endocrinology, 2021)
Newly emerging evidence has implicated that progesterone receptor component 1 (PGRMC1) plays a novel role not only in the lipid disturbance induced by atypical antipsychotic drugs (AAPD) but also in the deterioration of glucose homoeostasis induced by chronic clozapine treatment. The present study aimed to investigate the role of PGRMC1 signaling on hepatic gluconeogenesis and glycogenesis in male rats following chronic clozapine treatment (20 mg/kg daily for 4 weeks). Genetic tools named recombinant adeno-associated viruses were constructed for the knockdown or overexpression of hepatic PGRMC1 expressions. Meanwhile, AG205, the specific inhibitor of PGRMC1 was also used for functional validation of PGRMC1. Hepatic protein expressions were measured by western blotting. Simultaneously, plasma glucose and insulin, HbA1c, hepatic glycogen were also determined by assay kits. Additionally, concentrations of PROG in plasma, liver and adrenal gland were measured by a liquid chromatography-tandem mass spectrometry method. Our study demonstrated that clozapine promoted the process of gluconeogenesis and repressed glycogenesis, respectively mediated by PI3K-Akt-FOXO1 and GSK3β signaling via inhibition of PGRMC1-EGFR/GLP1R in rat liver, along with an increase in fasting blood glucose, HbA1c levels and a decrease in insulin and hepatic glycogen levels. Furthermore, in rats, knockdown or inhibition (specific inhibitor, AG205) of PGRMC1 mimics, whereas its overexpression moderately alleviates clozapine-induced glucose disturbance by upregulating the expression of PGRMC1-EGFR/GLP1R-PI3K-Akt pathway. Potentially, the PGRMC1 target may be regarded as a novel therapeutic strategy for AAPD-induced metabolic adverse effects.